PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) SEBAGAI UPAYA MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR BIOLOGI SISWA KELAS VIII B SMP NEGERI 22 KOTA BENGKULU - Idrus, Irdam; Zukmadini, Alif Yanuar (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
This study aimed to describe the activities of teachers and students as well as the student’s biology learning outcomes using the cooperative learning model TSTS type (two stay two stray). This type of research is a classroom action research (CAR), which was conducted in two cycles. Each cycle consists of the planning, implementation observation , and reflection. Research subjects are biology teachers and students of SMP Negeri 22 Kota Bengkulu Class VIIIB. Instruments used are observation sheets to determine the activities of teachers and students, as well as sheets and worksheets test to determine learning outcomes. Data were analyzed by calculating the results of observations the average value and determine the range of each criterion. Learning outcomes data werw analyzed by calculating the value of the average gread and the percentage of mastery learning classical. The results of the analysis of observational data teacher activity cycle, obtained an average score of 39 (good) and in the second cycle to 41 (excellent). For student activity, the average score on the first cycle is 37.5 (good) and in the second cycle to 41 (excellent). First cycle average grade is 77.7 with a percentage of 80.95% completeness (completed) and the second cycle average value being 79.9 class with 85.71% percentage of completeness (completed). Concluded the activitas of teachers and students is improving well and the results obtained by studying biolgy have achieved mastery learning through the application of the classical cooperative TSTS type in class VIIIB SMP Negeri 22 Kota Bengkulu. Keywords : Cooperative Two Stay Two Stray (TSTS), Learnin activities, outcomes learning